Development of a tool to measure patient expectations with complete removable dentures - Ahmed, Rukshana (South African Dental Journal, 2020)
INTRODUCTION: Patients’ expectations of complete removable dentures may play a role in determining their level of satisfaction with newly constructed complete removable dentures. AIMS AND OBJECTIVES: To develop a Patient Expectation Questionnaire using a validated satisfaction questionnaire as framework and subsequently determine patients’ expectations of complete removable dentures. OBJECTIVES: 1. To formulate a patient expectations questionnaire using a validated satisfaction questionnaire framework-that will assesses their perceptions of new dentures 2. To determine patient expectations related to masticatory functional, pain, psychological discomfort and social disability with complete removable dentures. METHODOLOGY: All the aspects of the newly formed Patient Expectation Questionnaire (PEQ) was formulated following the framework of the OHIP-20 patient satisfaction tool. The expectation questionnaire was administered to patients at their first dental visit with the information sheet and informed consent form. RESULTS: A series of statistical tests was done to assess the validity and reliability of the Patient Expectation Questionnaire. These tests concluded that the newly formulated questionnaire was reliable. CONCLUSION: Patient expectations can be determined prior to treatment thereby allowing the clinician to manage these expectations and strive to meet the attainable ones during the construction of the complete removable denture. Amongst others masticatory efficiency and pain were identified as being high on the request list for new complete removable dentures.